Low concentration fe-doped alumina catalysts using sol-gel and impregnation methods: the synthesis, characterization and catalytic performance during the combustion of trichloroethylene - Solís Maldonado, Carolina; Rivera de la Rosa, Javier; Lucio Ortiz, Carlos J.; Hernández Ramírez, Aracely; Castillón Barraza, Felipe F.; Valente, Jaime S. (2014)
The role of iron in two modes of integration into alumina catalysts was studied at 0.39 wt% Fe and tested in trichloroethylene combustion. One modified alumina was synthesized using the sol-gel method with Fe added in situ during hydrolysis; another modification was performed using calcined alumina, prepared using the sol-gel method and impregnated with Fe. Several characterization techniques were used to study the level of Fe modification in the γ-Al2O3 phase formed and to correlate the catalytic properties during trichloroethylene (TCE) combustion. The introduction of Fe in situ during the sol-gel process influenced the crystallite size, and three iron species were generated, namely, magnetite, maghemite and hematite. The impregnated Fe-alumina formed hematite and maghemite, which were highly dispersed on the γ-Al2O3 surface. The X-ray photoelectron spectra (XPS), FT-IR and Mössbauer spectroscopy analyses revealed how Fe interacted with the γ-Al2O3 lattice in both catalysts. The impregnated Fe-catalyst showed the best catalytic performance compared to the catalyst that was Fe-doped in situ by the sol-gel method; both had better catalytic activity than pure alumina. This difference in activity was correlated with the accessibility of the reactants to the hematite iron species on the surface. The chlorine poisoning for all three catalysts was less than 1.8%.